2014
DOI: 10.5001/omj.2014.107
|View full text |Cite
|
Sign up to set email alerts
|

Starvation Based Differential Chemotherapy: A Novel Approach for Cancer Treatment

Abstract: Cancer patients undergoing chemotherapy treatment are advised to increase food intake to overcome the therapy-induced side effects, and weight loss. Dietary restriction is known to slow down the aging process and hence reduce age-related diseases such as cancer. Fasting or short-term starvation is more effective than dietary restriction to prevent cancer growth since starved cells switch off signals for growth and reproduction and enter a protective mode, while cancer cells, being mutated, are not sensitized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 68 publications
(84 reference statements)
1
23
0
Order By: Relevance
“…Stress-induced autophagy is an important protective strategy that can maintain cell survival, which ultimately results in drug resistance in various types of tumor cells. 38 In this study, DCA treatment inhibited cellular autophagy and promoted apoptosis. RARA, an autophagy activator, can render the cells more resistant to DCA, indicating that DCA causes cell death by disrupting cancer cell metabolism and inhibiting autophagy.…”
Section: Discussionmentioning
confidence: 61%
“…Stress-induced autophagy is an important protective strategy that can maintain cell survival, which ultimately results in drug resistance in various types of tumor cells. 38 In this study, DCA treatment inhibited cellular autophagy and promoted apoptosis. RARA, an autophagy activator, can render the cells more resistant to DCA, indicating that DCA causes cell death by disrupting cancer cell metabolism and inhibiting autophagy.…”
Section: Discussionmentioning
confidence: 61%
“…Autophagy is an evolutionarily conserved catabolic pathway where cells deliver their own cytoplasmic material and/or organelles to lysosomes for degradation[ 9 ]. Accumulating evidence shows that the increased level of autophagy induced by chemotherapy contributes to tumor MDR[ 24 ]. Autophagy serves as an adaptive stress response in tumor cells that facilitates their survival in settings of increased metabolic demand, hypoxic microenvironments, or cancer therapies[ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also showed that tumor suppressor genes, daf-16/ Foxo, daf-18/Pten, and lin-35/Rb are required for promoting C. elegans starvation survival (Baugh and Sternberg 2006;Cui et al 2013). Starvation or fasting has recently been investigated in cancer therapy (Naveed et al 2014;Cangemi et al 2016), as tumor cells are thought to be more susceptible to starvation due to the Warburg effect (Iansante et al 2015). Results from this study and previous work using C. elegans may suggest that cancer cells, that commonly harbor mutations in tumor suppressor genes, are highly sensitive to starvation stress.…”
Section: Discussionmentioning
confidence: 99%